Improvement of Renal Diet Knowledge among Hemodialysis Patients through Health Education in Commemoration of World Kidney Day - Elpiani Br Depari; Gabriella Janelisa Samosir; Betaria Sihombing; Yoga Wijaya; Ramaida Ginting (JURNAL PENGMAS KESTRA (JPK), 2026)
Chronic kidney disease (CKD) is a growing public health problem, with many patients eventually requiring hemodialysis therapy. Dietary management is an essential component of hemodialysis care, as it helps maintain fluid balance, nutritional status, and prevent disease-related complications. This community service activity was conducted in commemoration of World Kidney Day on March 12, 2026, at the Hemodialysis Unit of Grandmed Hospital Lubuk Pakam and involved 50 patients undergoing routine hemodialysis. The program consisted of health education delivered through interactive lectures, discussions, and question-and-answer sessions covering renal diet principles, fluid intake management, and restrictions on sodium, potassium, and phosphorus intake. Participants’ knowledge was evaluated using pre-test and post-test questionnaires. Most participants were male (52%), aged 30–59 years (64%), had completed senior high school or higher education (74%), and had been receiving hemodialysis for more than 18 months (58%). The evaluation results showed an increase in the proportion of participants with a good level of knowledge from 86% before the educational intervention to 98% afterward. However, misconceptions regarding fluid restriction and the consumption of high-phosphorus foods were still identified among some participants. These findings indicate that health education contributes to improving patients’ knowledge of renal dietary management and should be implemented continuously to support disease management and enhance the quality of life of patients undergoing hemodialysis.